Utilization of ICT Skills on Library Information Resources By Students At Kabale Brainstorm High School. - Twongyeirwe, Esther (Kabale University, 2023)
The study was about the utilization of ICT skills in library and information resources by students at Kabale Brainstorm High School. The study adopted a descriptive research design. A sample size of 200 respondents was used. Both questionnaires and interview guides were used to collect data. The study findings indicated that Computers, Scanners, Bar code readers, CD-ROM, Machines for Photocopying, Digital cameras and CCTV cameras, Networked Servers, and LDC Projector were identified by all respondents as ICT facilities available at Kabale Brainstorm High School. The study findings indicated that Newspaper/magazines, Reference materials (e.g. dictionaries, encyclopedias), Theses/dissertations, Pamphlets, Electronic Information Resources ( e.g. e¬journals), and Monographs/textbooks were the most information resources with a high extent of utilization at Kabale Brainstorm High School. The study findings also indicated that slow internet speed and insufficient internet access points, short duration of book loans, power outages, lack of library orientation, poor computer skills, lack of enough time, lack of adequate numbers of personal computers, and paying online services were the challenges encountered by students in library information resources utilization at Kabale Brainstorm High School. From the study findings, training of library users, availability of computer technology maintenance policy documents, providing user accounts for easy access to library resources and regular power supply, provision of current and up-to-date computer technology equipment, and provision of internet services were some strategies to be put in place to address the challenges encountered by students in library information resources utilization at Kabale Brainstorm High School.